Efectos del entrenamiento al fallo para la hipertrofia muscular en deportistas. - Tovar Calderón, Carlos Ignacio (2024)
Failure training, in the context of physical exercise, is a training technique that involves performing repetitions of an exercise until the muscle can no longer complete another repetition with good technical form. In other words, the person continues with the exercise until the muscle is completely fatigued. This method aims to stimulate muscle fibers to the maximum, thus promoting muscle growth and strength. The present research is a documentary-type bibliographic review aimed at determining the effects of failure training on muscle hypertrophy in athletes through the compilation of information to support its benefits. The research was carried out through a bibliographic analysis using 35 scientific articles with a time period between the years 2018 and 2023, obtained from scientific databases and high- impact journals which correspond to randomized clinical trials. Additionally, the articles were evaluated to validate their methodological quality using the PEDro scale, which obtained a score equal to or greater than 6. It was determined that failure training does not produce significant differences compared to training that does not reach muscular failure in terms of hypertrophy. Additionally, it was observed that these small differences are minimally affected by training variables such as load, number of repetitions, or volume.